Implementasi Model Problem Based Leraning (PBL) Pendekatan Culturally Teaching (CRT) Untuk Meningkatan Literasi Numerasi - Ayu Balisa, Novi; I Nyoman Sulastra; Novi Ayu Balisa (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This research aims to increase the numeracy literacy of class The main problem faced is the low numeracy literacy of students due to limited learning models and learning approaches that are not relevant to the cultural context. The subjects of this research were 36 students in class X-5. This research uses the Classroom Action Research (PTK) method which is carried out in two cycles. Each cycle consists of four stages, namely planning, action, observation and reflection. Data collection techniques include written tests, observation, interviews and documentation studies. The research results showed a significant increase in students' numeracy literacy abilities. In the pre-action, the average student score was very low with a completion rate of 17%. after implementing the CRT PBL approach in the first cycle, the average score of students' numeracy literacy was 32%. then the average score in the second cycle with completeness reached 61%. The conclusion of this research is that the application of the PBL learning model with the CRT approach can improve students' numeracy literacy.